Overcoming the Crisis of Guidance and Counseling Teachers for Service Efficiency in Secondary Schools in Jayapura City - Habel Saud; Yulius Mataputun; Yansen Alberth Reba; Mikhael Udam; Sally Putri Karisma; Listini Bestina Kamarea; Andika Ari Saputra (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2024)
This seminar aims to overcome the crisis of the shortage of guidance and counseling (BK) teachers in Jayapura City and improve the efficiency of counseling services in schools, especially with the increasing student ratio. Through this seminar, it is expected to create a deep understanding of the importance of efficient counseling services by optimizing collaboration between counseling teachers, subject teachers, parents, and related professionals. The method of conducting the seminar included lectures, discussions, and questions and answers, and went through three main stages: preparation, implementation, and evaluation. The targets of the activity were counseling teachers at junior high, high school, and vocational school levels in Jayapura City. From the results of the evaluation, which included five questions, an average score of 80% was obtained, indicating an increase in participants' understanding of the importance of technology utilization in counseling services and the need for cross-party collaboration to support the smooth and efficient counseling services in schools. This activity indicates that the seminar contributed positively to improving the professional competence of counseling teachers, as well as strengthening systematic support for counseling services in schools to effectively reach more students.